Proces skrócony przed biskupem - Nowicka, Urszula (Ius Matrimoniale, 2016)
From December 8, 2016 is in force motu proprio of Pope Francis Mitis Iudex Dominus Iesus. One of the biggest news is the introduction of the briefer Matrimonial Process before the Bishop. The essence of this process is simple and easy procedure. It is possible in those cases where the alleged nullity of marriage is supported by particularly clear arguments. “The diocesan bishop himself is competent to judge cases of the nullity of marriage with the briefer process whenever: 1° the petition is proposed by both spouses or by one of them, with the consent of the other; 2° circumstance of things and persons recur, with substantiating testimonies and records, which do not demand a more accurate inquiry or investigation, and which render the nullity manifest” (kan. 1683 MIDI). The purpose of this article is to analyze the new norms.